New approaches for the sustainable management of Neopestalotiopsis clavispora, the causal agent of strawberry crown and root rot in Tucumán, Argentina = Nuevos enfoques para el manejo sustentable de Neopestalotiopsis clavispora, agente causal de la Podredumbre de raíces y corona de la frutilla en Tucumán, Argentina - Ramallo, Ana Carolina; Namen, Santiago; Salazar, Sergio Miguel; Heredia, Ana Micaela; Kirschbaum, Daniel Santiago (Facultad de Agronomía, Zootecnia y Veterinaria, Universidad Nacional de Tucumán, 2025)
The disease caused by Neopestalotiopsis clavispora in strawberries is responsible for severe damage and is considered an emerging threat worldwide. It was first identified as causing significant losses in commercial fields in Argentina in 2016. This study aimed to evaluate the efficacy of various biological control agents for managing N. clavispora within a sustainable strawberry crop management framework. The effectiveness of Bacillus methylotrophicus, Azospirillum argentinense REC3, two strains of Trichoderma, and a low-toxicity inorganic compound against the pathogen was assessed through in vitro and in vivo assays. Additionally, the resistance of 11 commercial strawberry cultivars to the pathogen was investigated using artificial inoculations. The results showed that, in vitro, both Trichoderma strains exhibited higher inhibition of N. clavispora (87-90%) compared to B. methylotrophicus (61%). Regarding cultivar performance, significant differences in disease severity were observed after artificial inoculations on detached leaves. The cultivars Sabrina, Sayulita, San Andreas, and Sahara exhibited foliar damage levels below 20%. Preventive applications of Trichoderma improved root length, and fresh and dry root weight, with mild symptoms similar to that of the fungicide Bellis® used as a chemical control. Applications of A. argentinense REC3 significantly reduced disease severity with and also enhanced leaf biomass, increasing aerial fresh and dry weight as well as the leaf area index. These findings provide valuable insights for developing integrated management strategies for this disease, ensuring environmental sustainability, maintaining fruit quality, and preserving biodiversity in strawberry production agroecosystems.